Protective effect of dexmedetomidine on lung injury during one-lung ventilation in elderly patients undergoing radical esophagectomy - Juanjuan Miao; Mengmeng Cai; Jiafeng Sun; Yi Gu; Boxiang Du (Universidade de São Paulo, 2023)
Abstract This study investigated the protective effect of dexmedetomidine (Dex) on lung injury during one-lung ventilation (OLV) in elderly patients undergoing radical esophagectomy with remote ischemic preconditioning (RIPC). Fifty-four esophageal cancer patients undergoing radical esophagectomy were divided into control, RIPC and RIPC+Dex group. During the anesthesia and ventilation in surgery, the RIPC was performed in RIPC group, and the intravenous infusion of Dex based on RIPC was conducted in RIPC+Dex group. At the time immediately before OLV beginning (T1), 60 min of OLV (T2) and end of surgery (T3), the oxygenation index (OI) and respiratory index (RI) were recorded, and the serum superoxide dismutase (SOD), malondialdehyde (MDA), tumor necrosis factor α (TNF-α) and interleukin 6 (IL-6) levels were determined. Results showed that, compared with RIPC group, in RIPC+Dex group the OI at T2 and T3 increased, the RI at T2 and T3 decreased, the serum SOD level at T3 increased, the serum MDA level at T3 decreased, the serum TNF-α and IL-6 levels at T2 and T3 decreased (all P < 0.05). In conclusion, for elderly patients undergoing radical esophagectomy with RIPC, Dex can effectively inhibit the oxidative stress and inflammatory response during OLV, thus alleviating the lung injury and reducing the postoperative complications.